Inserç\~ao no mercado de trabalho: Diferenças por sexo e conseqüências sobre o bem-estar - Ricardo Paes de Barros; Carlos Henrique Corseuil; Daniel Domingues dos Santos; Sergio Firpo (Instituto de Pesquisa Econômica Aplicada (IPEA), 2001)
– In the recent period, the qualitative dimension of the women participation in the labor force has improved quickly, in response to cultural and economic changes. In Brazil, many authors have pointed that women have a higher level of schooling than men, which should result, caeteris paribus, in better professional opportunities. However people claim that it is not observed neither in Brazil nor anywhere else, which results in a welfare loss. It's interesting to study how the welfare would change if the women and men have the same chances in the job market. In this paper, we propose how to simulate this hypothetical world. We found that the increase in the women's participation in the labor market would generate just an insignificant effect over the familiar welfare.
Keywords: 330; Weibliche Arbeitskräfte; Brasilien